2020
DOI: 10.1177/1049732319900164
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Perspectives About Health to Orient Obesity Intervention Among Urban, Transitionally Housed Indigenous Children

Abstract: Drawing from a socioecological framework of health, this community-based participatory research study examined key cultural health perspectives of transitionally housed, food insecure Indigenous children (aged 8–12 years) by utilizing talking circles and a 4-day photovoice (PV) curriculum. In total, 18 Indigenous children portrayed their health perceptions by taking photographs of their living environment and categorizing photos as healthy, unhealthy, or mixed. And, 10 of the 18 children completed pre- and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(48 citation statements)
references
References 55 publications
(73 reference statements)
0
47
0
1
Order By: Relevance
“…Land then serves as an active agent in healing, provides a culturally appropriate location to conduct a healing, and supports the common factors of healing found in most health interventions around the world (Johnson-Jennings et al 2020b). Even more, Indigenous land-based initiatives are entrenched within community knowledge, guided by community elders and knowledge keepers, and often arise from the community as grassroots initiatives, sometimes in partnership with Indigenous and allied scientists (see Billiot 2017;Jennings et al 2019;Jennings et al 2020;Jennings and Lowe 2014;Walters et al 2011;Walters et al 2018). Thus, engaging upon the land can serve as a potentially effective and sustainable approach to health.…”
Section: Land As An Appropriate Healing Context For Houmamentioning
confidence: 99%
See 1 more Smart Citation
“…Land then serves as an active agent in healing, provides a culturally appropriate location to conduct a healing, and supports the common factors of healing found in most health interventions around the world (Johnson-Jennings et al 2020b). Even more, Indigenous land-based initiatives are entrenched within community knowledge, guided by community elders and knowledge keepers, and often arise from the community as grassroots initiatives, sometimes in partnership with Indigenous and allied scientists (see Billiot 2017;Jennings et al 2019;Jennings et al 2020;Jennings and Lowe 2014;Walters et al 2011;Walters et al 2018). Thus, engaging upon the land can serve as a potentially effective and sustainable approach to health.…”
Section: Land As An Appropriate Healing Context For Houmamentioning
confidence: 99%
“…By systematically removing Indigenous peoples from their ancestral lands, connections to ancestral wisdom and the transmission of Indigenous cultural protective factors have been severely disrupted (Baskin 2016;Jennings et al 2020;Walters et al 2011). This settler colonialism has been described as a systematic imperial act of taking territory by force in distant lands and replacing the population with new settlers (Wolfe 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Socio-ecological models have been used analytically in health research to examine the diverse influences on people's health seeking practices (Casey et al, 2009;Jennings et al, 2020;Muller et al, 2019;Wheeler & Early, 2018).These models have facilitated exploration of interpersonal, institutional and public policy influences on key populations' access to HIV prevention, testing, treatment and care many international settings (Lazuardi et al, 2020;Mitchell et al, 2019;Whitford et al, 2021) including Uganda (Nakiganda et al, 2021;Tumwine et al, 2019Tumwine et al, , 2020. Socio-ecological models have predominantly been used to examine barriers to accessing services.…”
Section: Introductionmentioning
confidence: 99%
“…This attendance to the holistic needs of behavioral health clients may reflect ideas that go beyond treatment to become a form of holistic healing and fostering of all-around wellbeing. Such models and understandings have been suggested as especially relevant to American Indian clients and communities in past research (e.g., see Gone, 2009; Jennings et al, 2020), and it is possible these values are being demonstrated in practice today at some level at these Urban Indian Health Programs.…”
Section: Discussionmentioning
confidence: 99%